Ethical Tourism Development: An Ecotourism Perspective in Jamaica Kincaid’s Travel Narrative - Upadhyay, Toya Nath (SCHOLARS: Journal of Arts & Humanities, 2024)
This study reads Jamaica Kincaid’s travel narrative A Small Place (1988) from the ecotourism perspective. The narrative paints a bleak portrait of the post-independent Antigua that has been promoting capitalism vis-a-vis the government ministers and foreign traders consequently engulfing the gap between the rich and the poor, and the tourists and the hosts. The author deplores the way the government has fostered tourism, which, bourgeoned along with the rise of capitalism, has sustained neocolonialism by adversely disrupting the environmental, economic, and social aspects of Antigua. Due to the deleterious consequences of tourism, the author expresses her vile rant on the tourists (who belong to the white race) relegating them to ugly human things. She describes them as choosy to see certain things. Here, this raises a question: why does the author dehumanize the tourists as ugly things who see only certain things not others? The study resolves this question that the author reduces the tourists to that position because they perpetuate their forefathers’ masterly position in gazing the native Antiguans as servants. They see only those things that they like to see from the perspective of the tourist gaze. For the analytic purpose, the study engages theoretical insights from scholars in the ecotourism perspective such as Martha Honey, Robert Fletcher and others, which as propounded by these scholars, promotes responsible and ethical tourism by underscoring environmental conservation, economic development, and respect to native peoples and their cultures. Finally, the study concludes that Kincaid denounces the ongoing trends in tourism that are thoroughly adverse for Antiguan environment and people. She urges the tourists to get transformed from ugly human things to human beings by discarding their self-proclaimed master’s yoke. The study expects to add a critical reading into Kincaid’s narrative, as well as into the area of ecotourism.